2012
DOI: 10.1016/j.exer.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Graft survival and endothelial outcomes in the new era of endothelial keratoplasty

Abstract: Corneal endothelial cells do not proliferative in vivo sufficiently to enable endothelial regeneration, and thus diseases of the corneal endothelium, which cause poor vision and discomfort, require treatment by transplantation of cadaveric donor corneal endothelial cells. The two major goals of any corneal transplant procedure are to restore vision and to promote longevity of the donor cornea by maintaining a healthy donor endothelial cell density. Over the last decade, the surgical treatment for endothelial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 100 publications
(172 reference statements)
0
72
0
4
Order By: Relevance
“…[12][13][14] With endothelial keratoplasty continually evolving, it will be pertinent to establish the role of combined cataract surgery in these newer techniques. 14,15 In conclusion, mean ECL and complication rates were comparable at 6, 12 and 24 months in routine cases undergoing concurrent DSEK with cataract surgery and those undergoing DSEK. To our knowledge, this is the largest UK data series reporting ECCs.…”
Section: Discussionmentioning
confidence: 71%
“…[12][13][14] With endothelial keratoplasty continually evolving, it will be pertinent to establish the role of combined cataract surgery in these newer techniques. 14,15 In conclusion, mean ECL and complication rates were comparable at 6, 12 and 24 months in routine cases undergoing concurrent DSEK with cataract surgery and those undergoing DSEK. To our knowledge, this is the largest UK data series reporting ECCs.…”
Section: Discussionmentioning
confidence: 71%
“…6,[15][16][17] Corneal transplantation performed as a DSEK procedure in the rabbit gave a successful graft in all cases, with a transparent cornea and no serious complications such as graft rejection, graft failure, or graft dislocation. Representative slit-lamp microscopic images showed attachment of the graft to the back side of cornea, and corneal transparency was maintained in the rabbit model 2 weeks after surgery (Fig.…”
Section: Immune Cells Infiltrate On the Corneal Endothelium Of Allogementioning
confidence: 99%
“…Corneal transplantation has been accepted as a successful procedure, but several large cohort studies have now shown that graft survival after 10 years following penetrating keratoplasty (PK) is only approximately 50%, [3][4][5] although this varies widely depending on the indications and the specific studies. 6,7 Endothelial dysfunction also accounts for 50% of the total graft failures, suggesting that corneal endothelial damage is the leading cause of graft failure. 5,7 Endothelial graft failure can be divided into three types: primary graft failure (mainly iatrogenic), immunologic rejection, and late endothelial failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, worldwide cornea donor shortages, chronic graft failure due to long-term continuous cell loss after transplantation, and difficulties in surgical procedures for endothelial keratoplasties are still problems that limit the effectiveness of these procedures in the clinical setting. 8,9 This has prompted efforts to develop tissue-engineering therapies that can overcome the problems associated with conventional corneal transplantation.…”
mentioning
confidence: 99%